P1-S2.41 Sentinel survillance for pharyngeal chlamydia and gonorrhoea among men who have sex with men - San Francisco, 2010. (10th July 2011) - Park, J; Marcus, J; Bernstein, K; Pandori, M; Snell, A; Philip, S
Abstract : Background: Although a potentially important route for transmission, limited data exist on the burden of pharyngeal chlamydia (CT) and gonorrhoea (GC) among men who have sex with men (MSM). The San Francisco Department of Public Health has recommended nucleic acid amplification test (NAAT)-based pharyngeal screening for MSM since 2005. We examined pharyngeal CT and GC among MSM participating in the STD screening program in 2010. Methods: MSM seeking services at a variety of clinical sites provided clinician-collected pharyngeal specimens for APTIMA Combo 2 testing. The prevalence of pharyngeal CT and GC was estimated at five sentinel sites—the municipal STD clinic, a gay men's health clinic, an HIV care clinic, an HIV testing site, and primary care clinics supported by the San Francisco Department of Public Health. Positivity for each infection was calculated as the number of positive tests divided by the number of testers with corresponding CIs. Additionally, we calculated positivity and OR to determine whether the prevalence of pharyngeal CT and GC differed by HIV status among patients tested at the municipal STD clinic. Results: In 2010, over 12 000 pharyngeal specimens were tested for an overall CT positivity of 1.69% (95% CI 1.47 to 1.93) and GC positivity of 5.76% (95% CI 5.36 to 6.19). At the five sentinel sites, pharyngeal CT positivity ranged from 1.10% (HIV testing site) to 2.28% (STD clinic); pharyngeal GC positivity ranged from 3.4% (HIV testing site) to 7.01% (STD clinic). For tests conducted at the STD clinic among HIV-uninfected testers, pharyngeal CT positivity was 1.57% (95% CI 1.11 to 2.15) and pharyngeal GC positivity was 7.02% (95% CI 6.03 to 8.11). Among HIV-infected testers, the pharyngeal CT and GC positivity were 4.06% (95% CI 2.92 to 5.49) and 6.99% (95% CI 5.48 to 8.76), respectively. HIV-infected testers were more likely to have a positive pharyngeal CT test compared with HIV-uninfected testers (OR 2.65, 95% CI 1.65 to 4.27); there were no differences in pharyngeal GC positivity between HIV-infected and HIV-uninfected testers at the STD clinic. Conclusion: Sentinel surveillance data indicates that there is a substantial burden of pharyngeal CT and GC infections among MSM in San Francisco. Identification and treatment of pharyngeal infections could prevent ongoing transmission of these bacteria. Increasing access to NAAT-based pharyngeal screening should be a public health priority.